Avaliação do meio físico como ferramenta para a seleção adequada de área para instalação de aterro sanitário municipal: estudo de caso do CONCISSS, região nordeste do Estado do Pará - SOUSA, Tiago Marinho Pedroso (2024)
In the Northeast Region of the State of Pará, five cities signed the Intermunicipal Consortium called CONCISSS, for the installation of a sanitary landfill, which consists of Castanhal, Inhangapi, Santa Izabel do Pará, Santa Maria do Pará and São Francisco do Pará, among which, the municipality of Castanhal had seven areas previously selected to identify the most suitable for the installation of the sanitary landfill, meeting legal and regulatory requirements. In order to carry out the studies in the previously selected areas, the NBR 13,896 Standard of the Brazilian Association of Technical Standards - ABNT (1997) was applied, as well as the provisions provided for in the current legislation. To evaluate the physical, spatial and political aspects, tools were used in a Geographic Information System (GIS) environment, infiltration tests to evaluate the hydraulic conductivity of the vadose zone by the Open End Hole method, collection of sediment samples for granulometric and diffraction analysis. Rayx, in addition to dimensioning the landfill area for a minimum useful life for the period of 20 years (2021 to 2040). Within the GIS environment, it was possible to develop, in the seven previously selected areas, spatial analysis using remote sensing and geoprocessing of satellite images, in accordance with current regulations, highlighting the analysis of slope, land use, minimum distance from water courses and Permanent Protection Areas (APP), minimum distances to population centers, minimum distances from waste producing centers (CPL) and safe distances from road systems, considering that none of the seven areas satisfied these aspects of integral form. The average hydraulic conductivity (Kv) of areas 1, 2, 6 and 7 are in the order of 10-4 cm/s, and meet, with exceptions, the conditions provided for in the technical standard, and the other areas do not offer minimum conditions in this parameter. The soil of the city of Castanhal presents a predominance of two textural types, medium-clay and mediumsandy soil, being locally clayey. With regard to the mineralogical assemblage, the sediments are basically constituted by quartz, and occasionally lower levels of hematite and goethite, as well as trace minerals of anatase and illite, with the clay mineral kaolinite behaving with duality, sometimes in lower content and sometimes as a trace mineral. The data were gathered in a weighting matrix, and, in priority levels, considering the technical, economic, social and political aspects to propose final indices, with the evaluation of the areas, among which only areas 1 and 2 present conditions favorable for the practice of sanitary landfill, while areas 6 and 7 as moderately favorable; the others, areas 3, 4 and 5, presented at least one eliminatory criterion, considering them unfavorable for the installation of the sanitary landfill.